Effects of Stimulus Type and Level Repetition on Content-Level Binding in Global/Local Processing - Hübner, Ronald; Kruse, Rana (Frontiers in Psychology, 2011)
The processing and representation of hierarchical objects not only involves the identification of information at the different levels, but also the binding of the identified content to its respective level. Whereas identification is well understood, little is known about content-level binding. In a recent study, however, it has been shown that attentional priming of certain spatial frequencies is advantageous for this binding. Therefore, the present study investigated effects of related factors on the binding process, namely stimulus type (filled or outlined hierarchical letters), stimulus-type repetition, and target-level repetition. The results show that content-level binding was improved for outlined stimuli and after target-level repetition, whereas stimulus-type repetition had no effect. The data suggest that hierarchical stimuli are mentally represented by abstract level categories and that content is linked to these categories by means of level-specific and identity-specific spatial-frequency information.